Enhancing Students’ Speaking Skill through YouTube Video in Pandemic Era - Sudrajad, Wahyu; Jauhari, Iman; Pigai, Zeth K (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
The COVID-19 pandemic has profoundly impacted education, requiring innovative teaching methods to maintain students' engagement and learning outcomes. This research investigates the effectiveness of using YouTube videos as a tool to enhance students’ speaking skills in an online learning environment. Conducted with senior high school students, the study applied a mixed-method approach, combining pre-tests, post-tests, and qualitative observations. The findings reveal that YouTube videos significantly improved students' speaking skills by providing authentic materials, engaging content, and opportunities for self-paced learning. Furthermore, the students demonstrated increased motivation and confidence in speaking English. Challenges, such as internet accessibility and selecting appropriate video content, were also identified. This study concludes that YouTube videos can be an effective alternative teaching medium, particularly during times of limited face-to-face interaction, provided they are used strategically to align with learning objectives